مهارات الفراسة الابتكارية لدى طالبات قسم رياض الأطفال - رسول، لمياء سليم (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2022)
تعد قراءة الوجوه من أهم مهارات علم الفراسة التي تتطلب من الفرد نفسه المقدرة على مراقبة السمات الشخصية للأفراد الأخرين عن طريق ملاحظة مظاهر أو سمات وجوههم، وتشمل تلك المهارة معرفة العلاقة بين الخصائص أو سمات الشخصية بالاختلافات الجسدية التي تظهر على وجوه الناس؛ مثلا شكل الجبين والحاجبين وطبيعة وحجم ولون العينين والجفون والأنف والفم والفك والخدين والذقن والأذنين والشعر. وهذا ما يجعل من مهارة الفراسة الابتكارية احدى متطلبات التمكين المهني لدى الموظف الذي يتعامل مع الأخرين، ومن بينهم معلمة الروضة، فعن طريق مهارة الفراسة تستطيع معلمة الروضة التمييز بين مشاعر الابتسامة السعيدة والتعبير الغاضب التي تظهر في وجوه الأطفال، كما تتمكن من تحديد الأطفال الذين يشعرون بالمرض والأطفال الذين يشعرون بالتوتر نتيجة لرغبتهم في قضاء حاجتهم. لذا جاء البحث الحالي ليتعرف على الأهداف الأتية: 1- مهارات الفراسة الابتكارية لدى طالبات قسم رياض الأطفال. ٢- الفروق في مستوى مهارات الفراسة الابتكارية لدى طالبات قسم رياض الأطفال تبعا لمتغيري: أ- نوع المهارة (التعرف على تعابير الوجه، تفسير تعابير الوجه، الحل المناسب للتعابير الوجه السلبية). ب- نوع المرحلة الدراسية (الأول -الثاني -الثالث -الرابع). ومن أجل التوصل إلى نتائج أهداف البحث الحالي، قامت الباحثة ببناء اختبار يتألف من ثلاث مهارات والتي تحدد مهارات الفراسة الابتكارية كما ما جاء في النظرية الفسيولوجية للمنظر (لافاتير)، ووفقا لذلك، فقد تكونت فقرات الاختبار من (٢٤) فقرة مقسمة على ثلاثة مجالات. وكما قامت الباحثة أيضا بسحب (٣٠٠) طالبة من طالبات قسم رياض الأطفال بعدهن يمثلن (عينة التحليل الإحصائي) ومن ثم تم استخراج الخصائص السيكومترية للاختبار، إذ تم حذف (٤) فقرات منه. ومن ثم قامت الباحثة أيضا بسحب عينة أخرى بعدها تمثل (عينة التطبيق) والتي تم استخراج نتائج البحث عند طريق الاختبار عليها، وبعد تحليل إجابات العينة، كشفت نتائج البحث عما يأتي: 1- تمتع عينة البحث بمهارات الفراسة الابتكارية. 2- أن لمهارات الفراسة الابتكارية أثرا في تمتع العينة بالفراسة الابتكارية، وبشكل خاص في مهارة تفسير تعابير الوجه. 3- أن للمرحلة الدراسية أثرا في تمتع أفراد العينة بمهارات الفراسة الابتكارية، وبشكل خاص المرحلة الدراسية الثالثة. Face reading is one of the most important skills of physiognomy that requires the individual himself to be able to observe the personality traits of other individuals by observing the appearances or traits of their faces. This skill includes knowing the relationship between characteristics or personality traits with the physical differences that appear on people’s faces; For example, the shape of the forehead and eyebrows, the nature, size and color of the eyes, eyelids, nose, mouth, jaw, cheeks, chin, ears and hair. This makes the innovative physiognomy skill one of the requirements for professional empowerment of the employee who deals with others, including the kindergarten teacher. Through the skill of physiognomy, the kindergarten teacher can distinguish between the feelings of a happy smile and the angry expression that appears in the children’s faces, and she is also able to identify children who feel Illness and children who are stressed as a result of wanting to relieve themselves. Therefore, the current research came to identify the following aims: 1- Innovative Physiognomy skills among the Kindergarten Department students. 2- The differences in the level of innovative physiognomy skills among the students of the kindergarten department according to the two variables:- A- Type of skill (recognition of facial expressions, interpretation of facial expressions, appropriate solution to negative facial expressions). b- The type of school stage (first - second - third - fourth). In order to reach the results of the objectives of the current research, the researcher built a test consisting of three skills that determine the skills of innovative physiognomy as stated in the physiological theory of view (Lavater), and accordingly, the test items consisted of (24) items divided into three areas. The researcher also withdrew (300) female students from the Kindergarten Department after them representing (the statistical analysis sample), and then the psychometric characteristics of the test were extracted, as (4) items were deleted from it. Then the researcher also pulled another sample after it represented (the application sample), on which the results of the research were extracted by testing, and after analyzing the sample answers, the results of the research revealed the following: 1- The research sample has innovative physiognomy skills. 2- The skills of innovative physiognomy have an impact on the sample’s enjoyment of innovative physiognomy, especially in the skill of interpreting facial expressions. 3- The school stage has an impact on the sample members’ enjoyment of innovative physiognomy skills, especially the third stage of study.
Keywords: طلبة الجامعة -- الطلبة المعلمين -- معلمات الروضة -- السمات الشخصية -- الفراسة الابتكارية -- كلية التربية الأساسية -- الجامعة المستنصرية